LITERATURE REVIEW: POTENSI KOMBINASI MINYAK DAUN MINT DAN MINYAK JINTAN SEBAGAI TERAPI DISPEPSIA FUNGSIONAL - Fenska Seipalla (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Functional dyspepsia affects> 20% of the general population. The symptoms of functional dyspepsia are often associated with impaired quality of life of the patient. Until now, the treatment of functional dyspepsia is still controversial. Therefore, there needs to be a review of other alternative therapies, such as traditional medicine. The literature review shows that combination therapy of peppermint oil and caraway oil has synergistic activity because peppermint oil has spasmolytic properties and caraway oil plays a role in increasing smooth muscle tone so that it is effective in relieving pain and discomfort in patients with functional dyspepsia. Further research development with a larger scale and long term is needed to evaluate the effectiveness of this herbal therapy.